2019
DOI: 10.1016/j.ebiom.2019.10.009
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LSAMP-AS1 binds to microRNA-183–5p to suppress the progression of prostate cancer by up-regulating the tumor suppressor DCN

Abstract: Background: : Prostate cancer (PCa) is a leading cause of cancer-related death in males. Aberrant expression of long noncoding RNAs (lncRNAs) is frequently reported in human malignancies. This study was performed to explore the role of LSAMP-AS1 in epithelial-mesenchymal transition (EMT), proliferation, migration and invasion of PCa cells. Methods: : Initially, the differentially expressed lncRNAs in PCa were screened out by microarray analysis. The clinicopathological and prognostic significance of LSAMP-AS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…For the last few years, quantities of lncRNAs have been reported to be crucial regulators in cellular processes of various cancers [ 5 7 ]. For instance, a novel lncRNA LSAMP-AS1 is involved in PCa process via targeting miR-183-5p/DCN axis [ 8 ]. LncRNA RHPN1-AS1 has been claimed to accelerate the breast cancer development [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the last few years, quantities of lncRNAs have been reported to be crucial regulators in cellular processes of various cancers [ 5 7 ]. For instance, a novel lncRNA LSAMP-AS1 is involved in PCa process via targeting miR-183-5p/DCN axis [ 8 ]. LncRNA RHPN1-AS1 has been claimed to accelerate the breast cancer development [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the last few years, quantities of lncRNAs have been reported to be crucial regulators in cellular processes of various cancers [5][6][7]. For instance, a novel lncRNA LSAMP-AS1 is involved in PCa process via targeting miR-183-5p/DCN axis [8]. LncRNA RHPN1-AS1 has been claimed to accelerate the breast cancer development [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, past researches have shown that aberrant expression of miRNAs would contribute to malignant development of human HCC [ 23–25 ]. MicroRNA-183-5p (miR-183-5p), a novel cancer-related miRNA, has been identified to act as a critical player in multiple types of human malignancies, including pancreatic adenocarcinoma [ 26 ], prostate cancer [ 27 ], colorectal cancer [ 28 , 29 ], renal cell cancer [ 30 ] and non-small cell lung cancer [ 31 ]; nevertheless, its biological role in HCC remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%